Pojęcie pasja w ogłoszeniach o pracę polskich, niemieckich i amerykańskich przedsiębiorstw - Jędrzejczyk, Anna (Linguistische Treffen in Wrocław, 2024)
The article aims to analyze the differences in the lexical meanings, associations of the „typical” American keyword „passion” used in the job advertisements published in Poland und in Germany among the group of Polish and German students (referring to the theory of a locutionary and illocutionary act based on Austin, 1955). The way of interpreting this keyword has an impact on the student’s final decision to apply for a job in the given company (a perlocutionary act, based on Austin 1955). The differences in meaning were presented with the help of lexical analysis (using dictionaries) and an empirical research in which a group of Polish and German students of business and finance were asked about the supposed semantic meaning, associations and implicatures of this keyword in the job advertisements through interviews and questionnaires. The results of this analysis show the difference in the interpretations of this keyword by German and Polish students and can be explained by external factors (determinats) connected with the economic situation, historical background of the chosen countries (Germany and Poland) as well as the general attitude of society towards americanization. It has also occurred that internal factors/ individual traits of the respondents (so called: formants) (Bonacchi 2011: 10), which could have impact on understanding this keyword passion, were also different in the investigated groups of students, which shows that international companies should take into consideration not only external factors, but also individual traits of respondents while standardization of the employee value proposition in the given countries.